On local solutions of a mildly degenerate hyperbolic equation - Aassila, M; Kaya, D (Academic Press Inc, 1999)
In this work we prove the existence of a unique nonlocal solution for the vibrations of a nonhomogeneous stretched string in Sobolev spaces and without any smallness conditions on the size of the initial data. (C) 1999 Academic Press.
Keywords: Initial-Value-Problem